Prevention efforts of corona virus (covid-19): identify symptoms, prevent transmission with hand cleanliness caring, and making hand sanitizer in Bagan Deli village Medan Belawan - Maha, Hetty Lendora; Arianto, Anayanti Arianto; Reveny, Julia; Nazliniwaty (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Currently the Novel Corona virus outbreak is worrying many parties lately. Common signs and symptoms of Covid-19 infection include symptoms of acute respiratory disorders such as fever, cough and shortness of breath. Bagan Deli Village is a sub-district located in Medan Belawan District which has a very dense population compared to other urban villages. The level of awareness of the residents of this sub-district towards personal hygiene, especially hands is still very minimal, residents still don't really care that hands can be a very easy medium for spreading diseases, especially Covid-19 because hands often make contact with the environment. The method used in this service are provides education or counseling about Covid-19, namely general symptoms, how to avoid transmission, as well as the importance of maintaining hand hygiene to prevent the Covid-19 contagious disease, furthetmore socialization and practice of proper hand washing and video screening of hand sanitizer gel making. The results of this activity showed that as many as 20 residents were declared to understand and understand efforts to prevent the transmission of Covid-19, which can be seen from the results of the pre-test and post-test that were carried out during the educational activity.